ICT adoption framework for Philippine MSMEs - Cristobal, Ma. Theresa Datul (Animo Repository, 2012)
This paper deals with the examination of the current penal system being implemented by the government in certain offenses punishable by the Revised Penal Code. The author aims to introduce an alternative sentencing scheme with regard to property crimes of which their penalties are dependent on the amount of goods stolen, embezzled, etc. An overview of the current sentencing alternatives being implemented by other countries is likewise explained and its possible adoption by the government is assessed. Document research method, particularly making use of historical data, is used to determine how resistant the community is to a new scheme in the penal system and how effective it is in curbing crime and vindicating the offenders rights. A legislative bill is also proposed to give the legislators a spring board in the enactment and subsequent implementation of the alternative sentencing scheme.